Study of anaemia in type 2 diabetes mellitus and its correlation with albuminuria and eGFR - Sharma, Neha; Rawat, Sarita; Marwah, Sadhna; Verma, Vikas (International Journal of Research in Medical Sciences, 2023)
Background: Diabetes mellitus (DM) is a common metabolic disease. Anaemia is a common accompaniment to diabetes, particularly in patients with albuminuria or reduced renal function. Anaemia is more frequent and more severe at any level of glomerular filtration rate (GFR) in diabetics compared to nondiabetic patients. Methods: One hundred patients with type 2 diabetes mellitus were included in the study. Complete blood count, serum iron profile, ferritin, vitamin B12 and folate, kidney function tests and urine albumin creatinine ratio were assessed for these patients. Estimated glomerular filtration rate (eGFR) was calculated with MDRD-4 variable formula. Results: Fifty-four patients (54%) were found to be anaemic. Serum ferritin <50 µg/l was taken as cut off for defining iron deficiency anaemia. 21 patients had iron deficiency anaemia (IDA) and 33 had anaemia of chronic disease (ACD). Serum vitamin B12 and folate levels were within normal limits in all the patients. There was a rise in the prevalence of anaemia from 25.9% in patients with a normal ACR to 59.2% in those with microalbuminuria and to 75% in macroalbuminuria. Conclusions: Any degree of renal impairment and albuminuria are the risk factors for anaemia in these patients. Hence screening, characterization and treatment of aneamia in type 2 DM may be helpful in management of these patients.